(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The objective of this project is to develop and build an automated system for detecting and neutralizing missiles. This system is specifically engineered to identify and track the target (missile) while it maneuvers in various directions. The automated target destruction system tracks the missile’s trajectory and engages it by precisely aligning and firing onto the target. This system comprises an advanced sonar-based object tracking system that continuously monitors the target. Once the target is detected, it transmits the precise location of the target to a Central Control System. The Central Control System initiates the movement of the firing mechanism towards the target (missile). After correcting the orientation, it transmits the control command to the firing system in order to launch an attack on the target. This project utilizes an ultrasonic radar system and a DC geared motorpowered firing device that is connected to a Microcontroller based control unit. We choose the use of ultrasonic sensors due to their ability to cover a greater detecting distance and detect targets under various illumination circumstances, including both day and night. Microcontroller programming is accomplished using the Embedded ’C’ language. This article has undergone processing in order to minimize human labor and fully automate the missile system. This results in reduced human error and more precision in system processing. This survey outlines the many approaches to automating the missile guidance system using maneuverable actuators. The diverse concepts pertaining to the automation system and the design modules will facilitate the exploration of multiple approaches in relation to the automation system.